2014
DOI: 10.1107/s1399004714013868
|View full text |Cite
|
Sign up to set email alerts
|

Direct phase selection of initial phases from single-wavelength anomalous dispersion (SAD) for the improvement of electron density andab initiostructure determination

Abstract: A novel direct phase-selection method to select optimized phases from the ambiguous phases of a subset of reflections to replace the corresponding initial SAD phases has been developed. With the improved phases, the completeness of built residues of protein molecules is enhanced for efficient structure determination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…According to the structure of lysozyme, the Arg, Lys, and Asn amino acids are mainly located on the surface of lysozyme (Figure ). The CH groups of the three amino acids are dominant in all of the CH groups of the amino residues.…”
Section: Resultsmentioning
confidence: 99%
“…According to the structure of lysozyme, the Arg, Lys, and Asn amino acids are mainly located on the surface of lysozyme (Figure ). The CH groups of the three amino acids are dominant in all of the CH groups of the amino residues.…”
Section: Resultsmentioning
confidence: 99%
“…Model refinement based on known FHA domains was also unfeasible because of the variation in loop regions among FHA domains. Finally, the recently developed direct phase selection method 29 effectively resolved the ambiguity of SAD phases and generated optimized initial phases for structure determination. The new algorithm is particularly helpful in cases where only SAD data are available.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The selenium sites of SeMet tTIFA 1−150 were located with SHELX C/D/E, 26 and the initial phase was calculated by Phaser 27 followed by density modification with DM. 28 Then the optimal initial phases were determined by the direct phase selection method to reduce the phase ambiguity, 29 and subsequently, automated model building was performed with Buccaneer. 30 The model was further improved by conventional two-wavelength MAD data sets collected from optimized crystals.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…By introducing a SAD likelihood function to rank possible solutions from phenix.hyss, a study showed that in the case of CysZ multicrystal data (Bunkó czi et al, 2014) SAD likelihood ranking significantly improved the rate of success in finding the correct anomalous substructure in terms of both the strength of the anomalous signal and the number of crystals used to produce the merged data set. Another study introduces a direct phaseselection step prior to density modification (using RESOLVE or DM) that significantly improved the final experimental phases and the quality of the resulting electron-density maps (Chen et al, 2014).…”
Section: Phasing and Structure Solutionmentioning
confidence: 99%